Analisis Pembelajaran Tematik Siswa Kelas 3 SDN Tangerang III pada Era Pandemi - Magdalena, Ina; Akbar, Ahmad Alvinda; Wijaya, Arman (TSAQOFAH, 2022)
Integrated learning must be based on student learning needs, systematically in its development formative evaluation is needed to improve the quality of program instruction and be used as guidelines or materials to improve and refine or perfect the learning outcomes material. Implementation of formative evaluation at SDN Tangerang 3 on the subject of 25 students in learning mathematics, social sciences, natural sciences, etc. It is carried out with tests and non-tests, the test technique used is about multiple choice and explanations. The non-test technique uses a question and answer instrument, discussion and observation. The results of the research using formative evaluation in learning mathematics, social sciences, natural sciences, in 3rd grade elementary school proved effective based on the results of the pre-test and post-test.